2014
DOI: 10.1128/aem.00056-14
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Airborne MS2 Bacteriophage Generated from Human Saliva, Artificial Saliva, and Cell Culture Medium

Abstract: c Laboratory studies of virus aerosols have been criticized for generating airborne viruses from artificial nebulizer suspensions (e.g., cell culture media), which do not mimic the natural release of viruses (e.g., from human saliva). The objectives of this study were to determine the effect of human saliva on the infectivity and survival of airborne virus and to compare it with those of artificial saliva and cell culture medium. A stock of MS2 bacteriophage was diluted in one of three nebulizer suspensions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 56 publications
6
72
0
Order By: Relevance
“…; Zuo et al . ) showed that the aerosol produced by the Collison nebulizer at low RH had a mode size at approx. 30 nm, which corresponds with the size of a ‘naked’ MS2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…; Zuo et al . ) showed that the aerosol produced by the Collison nebulizer at low RH had a mode size at approx. 30 nm, which corresponds with the size of a ‘naked’ MS2 virus.…”
Section: Discussionmentioning
confidence: 99%
“…The sturdiness of this virus makes it a good choice for a variety of studies where highly stable viruses are needed. Previous studies have demonstrated that the infectivity of phage MS2 is not significantly affected by nebulization or sampling (5,20,21). While it may be a good surrogate candidate for some aerosol studies, its resistance to some stress factors, such as UV irradiation, also indicates that it may not always be the best representative.…”
Section: Figmentioning
confidence: 99%
“…Although the infectivity of phage MS2 was not significantly affected by nebulization and sampling (5,19,21), this may not be representative of all viruses. Indeed, the differences in structural components, including the presence or absence of an envelope or of protruding structures, may have a significant impact on the vulnerability of airborne viruses to their environment.…”
Section: Figmentioning
confidence: 99%
“…With an approximate particle size of 28 nm, MS2 is a bacteriophage that only infects male Escherichia coli (E. coli) bacteria (Davis, Sinsheimer, & Strauss, 1961). Since it does not infect humans and due to its robust survivability, MS2 is widely used as a surrogate in research of small airborne viruses (Dawson, Paish, Staffell, Seymour, & Appleton, 2005;Woo, Hsu, Wu, Heimbuch, & Wander, 2010;Zuo et al, 2014). Prior to the aerosol generation process, the lyophilized MS2 bacteriophage was rehydrated in 100 mL DI water to make a stock suspension with a titer of around 10 11 PFU/mL and used soon thereafter.…”
Section: Test Aerosolmentioning
confidence: 99%